2021
DOI: 10.29103/mjml.v4i1.2919
|View full text |Cite
|
Sign up to set email alerts
|

The Improving Students’ Mathematics Results and Interest Through Online-Based Flipped Classroom Models

Abstract: People know that the internet today has become an integral part of the lifestyle of various Indonesian community groups, but the results of surveys conducted by the Indonesian Internet Network Organizing Association are known to have access to educational pages are still very lacking. The online-based flipped classroom learning model is packaged to appeal to students and is a learning that adapts online learning in times of pandemic by directing students to utilize the internet for learning. This study was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…The choice of learning models or strategies has a considerable influence on improving learning outcomes (Ermawati et al, 2023). During flipped classroom learning, students are required to understand the material first before the learning process, so that students become more active when discussing in class (Hamidah & Kusuma, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of learning models or strategies has a considerable influence on improving learning outcomes (Ermawati et al, 2023). During flipped classroom learning, students are required to understand the material first before the learning process, so that students become more active when discussing in class (Hamidah & Kusuma, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The statement is in line with a study conducted by Syajili & Abadi (2021), with the findings that flipped classrooms proved effective in improving the conceptual understanding and confidence of pupils. Meanwhile, Hamidah & Kusuma (2021), argue that the flipping classroom accessed via the internet not only improves student learning interest but also improves learning outcomes. In the context of mathematics learning, this model has also been shown to improve students' mathematical, affective, and cognitive abilities as students get higher cognitive challenges in applying, analyzing, synthesizing, and performing evaluations in the classroom.…”
Section: Experimentation Of the Flipped Classroom Learning Model And ...mentioning
confidence: 99%
“…Sebenarnya terdapat beberapa model pembelajaran yang dapat digunakan untuk pembelajaran jarak jauh. Salah satunya adalah pembelajaran yang dilakukan oleh Hamidah & Kusuma mencoba untuk menggunakan model pembelajaran yang sesuai dalam pembelajaran jarak jauh, yatu dengan model pembelajaran Flipped Classroom (Hamidah & Kusuma, 2021). Penerapan flipped classroom ini digunakan berdasarkan penelitian terdahulu yang telah dilakukan dimana siswa diminta untuk mengisi kuisioner dan melakukan wawancara.…”
Section: Upaya Peningkatan Pembelajaran Jarak Jauh Untuk Mencegah Dan...unclassified
“…Although interest towards mathematics has been considered an important factor influencing participation and success in mathematic (Oluyemo et al, 2020), studies have shown that negative interest toward the learning of mathematics has been exhibited even by primary school pupils (Okenyi, 2023). However, learner-centred instructional strategies can improve and sustain students' interest in mathematics (Asmira et al, 2021;Fabarebo et al, 2023;Kihwele & Mkomwa, 2023;Ryan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%